MENGELOLA PLURALISMEMELALUI DIALOG ANTAR AGAMA (SEBUAH TINJAUAN TEORITIK) Managing PluralismThrough Interfaith Dialogue (a Theoretical Review) - Anas Aijudin (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2017)
Religious pluralismis a social reality, that must be accepted by any individual or community group. As a social fact, the management of religious pluralism is a shared responsibility of all citizens. One of the models of pluralism management is through interfaith dialogue. Interfaith dialogue is understood as a joint effort among followers of religion to understand each other. In the interfaith dialogue, honesty and openness are important requirements for reaching mutual agreement. Political identity based on religion which is a serious threat for religious pluralism can be managed through this interfaith dialogue.